1995
DOI: 10.1073/pnas.92.15.6996
|View full text |Cite
|
Sign up to set email alerts
|

The bacterial colicin active against tumor cells in vitro and in vivo is verotoxin 1.

Abstract: We have identified verotoxin 1 (VT1) as the active component within an antineoplastic bacteriocin preparation from Escherichia coli HSC10 studied over two decades. Recombinant VT1 can simulate the toxicity of anticancer proteins (ACP), and the antineoplastic activity of ACP (and VT1) was abrogated by treatment with anti-VTI antibody. Similarly, VT1 mimics the protective effect ofACP in a murine metastatic fibrosarcoma model. Prior immunization with VT1 B subunit prevents the effect ofVT1 or ACP in this model. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
61
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(61 citation statements)
references
References 50 publications
0
61
0
Order By: Relevance
“…Ovarian carcinoma cell lines show particular sensitivity to verotoxin in vitro. Multidrug-resistant (MDR) cell lines, expressing the MDR1 P-glycoprotein (P-gp) drug efflux pump, derived from these cells showed approximately 1000-fold increase in sensitivity to verotoxin in vitro (3). The increase in sensitivity was found to correlate with the increased synthesis of Gb 3 2 isoforms containing shorter fatty acids (4).…”
Section: Verotoxin (Vt)mentioning
confidence: 96%
See 3 more Smart Citations
“…Ovarian carcinoma cell lines show particular sensitivity to verotoxin in vitro. Multidrug-resistant (MDR) cell lines, expressing the MDR1 P-glycoprotein (P-gp) drug efflux pump, derived from these cells showed approximately 1000-fold increase in sensitivity to verotoxin in vitro (3). The increase in sensitivity was found to correlate with the increased synthesis of Gb 3 2 isoforms containing shorter fatty acids (4).…”
Section: Verotoxin (Vt)mentioning
confidence: 96%
“…Such tumors showed a noticeable increase in Gb 3 species that migrated more slowly on TLC, consistent with shorter chain fatty acid isoforms. Similarly, human astrocytoma cell lines, which show high sensitivity to verotoxin in vitro (6) and as nude mice xenografts in vivo (7), showed increased content of short chain fatty acid containing Gb 3 . The presence of the short chain fatty acid Gb 3 species was correlated with an altered intracellular trafficking of verotoxin within the sensitive cells, such that toxin was targeted to the endoplasmic reticulum, nuclear envelope, and nucleus, as opposed to the Golgi in cells deficient in such receptor isoforms (4).…”
Section: Verotoxin (Vt)mentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that ovarian-derived tumor cells were effectively killed by Stx1, and interestingly, multidrug resistant variants of these tumor cells expressed higher levels of Gb3 and were more sensitive to Stx1 [129]. Gb3 was expressed also in tumor vasculature, suggesting a potential role for Stx as an antiangiogenic agent [130].…”
Section: Exploitation Of Stx In Medicinementioning
confidence: 99%